2016
DOI: 10.3928/01477447-20151222-01
|View full text |Cite
|
Sign up to set email alerts
|

Bowing Fracture With Literature Review

Abstract: A 5-year-old boy was brought to the emergency department after a fall from a jungle gym. He had persistent pain and swelling of his left forearm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, there are a few cases in which reduction of the dislocation cannot be accomplished by a closed procedure because the interposition of soft tissues in the radiohumeral joint obstructed the reduction. Other authors reported the most common interposed factors were annular ligament and anterior capsules [13][14][15] . In our case, it was an annular ligament, which was confirmed on both MRI films and intra-operative expose.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, there are a few cases in which reduction of the dislocation cannot be accomplished by a closed procedure because the interposition of soft tissues in the radiohumeral joint obstructed the reduction. Other authors reported the most common interposed factors were annular ligament and anterior capsules [13][14][15] . In our case, it was an annular ligament, which was confirmed on both MRI films and intra-operative expose.…”
Section: Discussionmentioning
confidence: 93%
“…It can be detected if one carefully evaluates the radiographs of an injured elbow, taking into account the radiocapitellar line and the ulnar bow 12 . Such an irreducible traumatic dislocation can be easily missed and whose later detections are often diagnosed as a neglected Monteggia fracture [13][14][15] . The rate of missed injuries has been as high as 50% 16 .…”
Section: Introductionmentioning
confidence: 99%
“…They predominantly take place in the pediatric population where the radius and ulna are the most frequently described injury sites and often originate from a fall on the outstretched hand. Furthermore, bowing fractures of the forearm can occur either isolated or in conjunction with joint dislocation or a fracture of the accompanying bone [2] . Correct diagnosis has proven to be challenging due to the absence of a clear cortical defect on radiographic images, the possibility of the plastic deformity only being visible on a strict anteroposterior (AP) or lateral view and the lack of or late formation of periosteal callus formation [3] .…”
Section: Introductionmentioning
confidence: 99%